The role of spiritual formation in the education of modern human beings: A European Christian perspective - Necula, Constantin V. (HTS teologiese studies, 2021)
One of the most considerable changes in the contemporary European educational mentality is a person’s disconnection from spiritual life. Christian formation has been replaced with religious pluralism, in terms of syncretism influenced by global economic ideologies. Some consequences are low resilience and low spiritual resistance to contemporary challenges, associated with mental traumas or social behaviour deficits. Is it possible to restore the modern person’s spiritual education? There is no evolution in the modern individual’s social life without a horizon of spiritual expectation and fulfilment, different from the strictly material one. Moreover, conscious education cannot deprive people of cultivating the spiritual part of their consciousness from which the real values of existence are born. A series of arguments for renewing the relation between school and the mature, Scripture-based Christian thinking in the spirit of the European pedagogy are revealed by the factual historical analyses. Both Eastern and Western European experiences have met after 13 years of evolving into two antagonist geopolitical spheres. Their lessons in the education field could be an appropriate model, academically applied at the cultural mentality and the European pedagogy level.Contribution: With this study, I want to highlight the historical and conceptual frameworks of the Christian religious education meaning in the context of the rediscovery of Orthodox Christianity by the international theological culture in post-communism. Orthodox Christianity, forgotten in dictionaries and syntheses by the Western theological elite, brings in a spiritualisation of education according to the Lord Jesus Christ’s Gospel and not of the ideological cultural interests.